1998
DOI: 10.1210/jcem.83.8.5036
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Glucocorticoid-Induced Growth Suppression with Growth Hormone

Abstract: Growth failure is common during long term treatment with glucocorticoids (GC) due to blunting of GH release, insulin-like growth factor I (IGF-I) bioactivity, and collagen synthesis. These effects could theoretically be reversed with GH therapy. The National Cooperative Growth Study database (n = 22,005) was searched for children meeting the following criteria: 1) pharmacological treatment with GC and GH for more than 12 months, 2) known type and dose of GC, and 3) height measurements for more than 12 months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
13

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(49 citation statements)
references
References 32 publications
2
34
0
13
Order By: Relevance
“…Although compensatory growth often follows the cessation of GC therapy, children with systemic chronic inflammatory diseases subjected to long-term GC treatment may have reduced final height (14,15). Normalizing height in these children, even with concomitant therapy with high-dose recombinant GH, is not straightforward (16)(17)(18). Moreover, permanent growth impairment has been reported in children receiving alternate-day GC treatment (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Although compensatory growth often follows the cessation of GC therapy, children with systemic chronic inflammatory diseases subjected to long-term GC treatment may have reduced final height (14,15). Normalizing height in these children, even with concomitant therapy with high-dose recombinant GH, is not straightforward (16)(17)(18). Moreover, permanent growth impairment has been reported in children receiving alternate-day GC treatment (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that GR gene polymorphisms do not have a substantial effect on the sensitivity to GH in this group. The growth retarding effect of GCs, known from corticosteroid treatment, is caused by the inhibition of endogenous GH secretion, collagen synthesis, cartilage sulfation, chondrocyte mitosis, GH receptor binding, and insulin-like growth factor 1 activity (33). It should, however, be noted that growth retardation is only seen when supraphysiological doses of corticosteroids are used.…”
Section: Discussionmentioning
confidence: 99%
“…The recent report from the large National Cooperative Growth Study showed that, whereas there was a general trend in that the higher the glucocorticoid dose the more severe the growth retardation, children on an identical glucocorticoid dose could have growth velocities ranging from 0 to 15 cm/year (22). Such a wide and varying range of growth velocities may be the result of the differing underlying pathologies in the study patients rather than the glucocorticoid dosage.…”
Section: Discussionmentioning
confidence: 99%